Environmental degradation and inclusive human development in Sub-Saharan Africa - Simplice Asongu; Nicholas M. Odhiambo (African Governance and Development Institute (AGDI), 2018)
In the light of challenges to sustainable development in the post-2015 development agenda, this study assesses how increasing carbon dioxide (CO2) emissions affect inclusive human development in 44 countries in sub-Saharan Africa for the period 2000-2012. The following findings are established from Fixed Effects and Tobit regressions. First, unconditional effects and conditional impacts are respectively positive and negative from CO2 emissions per capita, CO2 emissions from liquid fuel consumption and CO2 intensity. This implies a Kuznets shaped curve because of consistent decreasing returns. Second, the corresponding net effects are consistently positive. The following findings are apparent from Generalised Method of Moments (GMM) regressions. First, unconditional effects and conditional impacts are respectively negative and positive from CO2 emissions per capita, CO2 emissions from liquid fuel consumption and CO2 intensity. This implies a U-shaped curve because of consistent increasing returns. Second, the corresponding net effects are overwhelmingly negative. Based on the robust findings and choice of best estimator, the net effect of increasing CO2 emissions on inclusive human development is negative. Policy implications are discussed.
Keywords: C52; O38; O40; O55; P37; 330; CO2 emissions; Sustainable development; Inclusiveness; Environmental policy; Africa